An exploration of the learning-teaching of English as a second language by non-native speakers - Mosito-Matheleli, Cina Patricia (School of Education, 2023)
This is an exploratory study of the teaching strategies of non-native speakers English who teach English as a second language in secondary schools. Classroom observations of three teachers were conducted. It was found that teaching and through English as a second language is not a single decisive factor in teaching and learning effectiveness. Other factors such as cultural norms and the teacher's choice of strategies could impinge on the quality and effectiveness the teaching-learning process